Pengaruh Organizational Commitment Terhadap Employee Performance Di Rumah Tahanan Kelas I Surakarta - Muhammad Hans Ziskind; Padmono Wibowo (JOURNAL SAINS STUDENT RESEARCH, 2023)
Organizational commitment plays an important role in employee performance. The purpose of this study is to determine how much influence organizational commitment has on employee performance. The method used in this study was quantitative and the sample used in this study totaled 37 employees in Class IA Surakarta detention center. The results of this study indicate that organizational commitment affects the performance of correctional officers in the Surakarta Class IA Detention Center. This study shows that there is an influence between organizational commitment and employee performance with a strong positive correlation.